The Influence of Supervision, Work Discipline and Occupational Safety & Health (K3) on Employee Productivity at PT. Tasma Puja, Kampar Regency - Hidayatullah, Muhammad Ridho; Garnasih, Raden Lestari; Rifqi, Ahmad (Journal Of Accounting Management Business And International Research, 2024)
This research was conducted at PT.Tasma puja, Kampar Regency. The purpose of this study was to determine the effect of supervision, work discipline and occupational health safety (K3) on employee productivity at PT Tasma Puja, Kampar Regency, both partially and simultaneously. The types of data used in this study consisted of primary data and secondary data with a total of 126 people and a sample of 51 respondents. Sampling was carried out using the census method. The analysis used in this study was Multiple Linear Regression Analysis using SPSS version 25. The results showed that partially the (t) test found that the variables of Supervision, Work Discipline and Occupational Health Safety (K3) had a positive and significant effect on Employee Work Productivity at PT. Tasma Puja, Kampar Regency. Simultaneously test (F) it is known that the variables of supervision, Work Discipline and Occupational Health Safety (K3) together have a positive and significant effect on Employee Work Productivity at PT.Tasma Puja Kampar Regency. Meanwhile, based on the results of the calculation of the Determination Coefficient, the R Square value is 0.770, which means that the effect of Work Discipline and Health Safety (K3) on Employee Productivity is 77%. While the remaining 23% is influenced by other variables not included in this study.